Effects of Cyanobacterial Soil Crusts on Surface Roughness and Splash Erosion. Issue 12 (27th December 2018) - Bullard, Joanna E.; Ockelford, Annie; Strong, Craig; Aubault, Helene
Abstract: Soil surface roughness (SSR) modifies interactions and feedback processes between terrestrial and atmospheric systems driven by both the abiotic and biotic components of soils. This paper compares SSR response to a low‐intensity multiday rainfall event for soils with and without early successional stage cyanobacteria‐dominated biological soil crusts (CBCs). A rainfall simulator was used to apply 2, 5, and 2 mm of rain separated by a 24‐hr period over 3 days at an intensity of 60 mm/hr. Changes in SSR were quantified using geostatistically derived indicators calculated from semivariogram analysis of high‐resolution laser scans. The CBCs were stronger and splash erosion substantially less than from the physical soil crusts. Prior to rainfall treatment, soils with CBCs had greater SSR than those without. The rainfall treatments caused the physical crusted soils to increase SSR and spatial patterning due to the translocation of particles, soil loss, and the development of raindrop impact craters. Rainfall caused swelling of cyanobacterial filaments but only a slight increase in SSR, and raindrop impact cratering and splash loss were low on the soils with CBCs. There is no relationship between random roughness and splash erosion, but an increase in splash loss was associated with an increase in topographic roughness and small‐scale spatial patterning. A comparison of this study with other research indicates that for rainfall events up to 100 mm, the effectiveness of CBCs in reducing soil loss is >80% regardless of the rainfall amount and intensity, which highlights their importance for landscape stabilization. Plain Language Summary: Human and ecological systems rely on soils for the provision of water and nutrients, to support plant growth, for regulation of the water cycle and for the storage of carbon. The stability of soil surfaces can be controlled by the presence of crusts . Physical crusts form in the response to rainfall events causing the soil to break down and compact. Biological soil crusts are formed when cyanobacteria, fungi, algae, lichens, and mosses grow and bind the soil together. Biological soil crusts are particularly important in arid and semiarid areas where they cover up to 70% of interplant spaces. However, little is known about how the crusts control infiltration, runoff, and soil erosion rates or which is more effective at stabilizing the soil surface. In this study we use high‐resolution laser scanning to characterize how the stability of the soil surface is controlled by both physical and biological crusts in response to different rainfall events. We discuss the differences in the between the two crusts and observe that biological soil crusts can reduce soil loss by greater than 80% regardless of the rainfall amount and intensity which highlights their importance for landscape stabilization. Key Points: Prior to rainfall, cyanobacterial soil crusts have higher soil surface roughness (SSR) than physical crusts SSR of physical soil crusts is highly responsive to low rainfall; SSR of cyanobacterial soil crusts is stable in response to low rainfall Splash loss is associated with topographic roughness and spatial patterning